2013
DOI: 10.1186/1687-6180-2013-111
|View full text |Cite
|
Sign up to set email alerts
|

FIR filter optimization for video processing on FPGAs

Abstract: Two-dimensional finite impulse response (FIR) filters are an important component in many image and video processing systems. The processing of complex video applications in real time requires high computational power, which can be provided using field programmable gate arrays (FPGAs) due to their inherent parallelism. The most resource-intensive components in computing FIR filters are the multiplications of the folding operation. This work proposes two optimization techniques for high-speed implementations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…This can be understood considering the large LUTs of modern FPGAs. However, it was not expected, as previous work showed that the shift-and-add approach was better for input word sizes larger than 8 bit in the case of multiple constant multiplication [15]. This can be explained by the fact that in this case, much more sharing is possible when multiplying with several constants.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This can be understood considering the large LUTs of modern FPGAs. However, it was not expected, as previous work showed that the shift-and-add approach was better for input word sizes larger than 8 bit in the case of multiple constant multiplication [15]. This can be explained by the fact that in this case, much more sharing is possible when multiplying with several constants.…”
Section: Resultsmentioning
confidence: 93%
“…The two methods are reviewed in detail in Section II, the first objective of this work being too explicit which technique works best in which context. We are aware of only two earlier comparisons of KCM and shift-andadd [14], [15], both limited to the case of multiple constant multiplication (MCM) of small integer constants.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of pipelining MCM blocks was studied in [8]. Heuristic and exact minimization methods to directly pipeline the MCM block were proposed [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, this type of operations has become very important mainly when the pipelined constant multiplication blocks are implemented in the increasingly demanded field programmable gate array (FPGA) platforms. This is due to the fact that logic blocks of FPGAs include memory elements, and thus, pipelining results in low extra cost [5][6][7][8][9][10][11][12]. Currently, the use of three-input adders has started to gain importance, since the logic blocks of the newest families of FPGAs are bigger and allow to fit more complex adders using nearly the same amount of hardware resources [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the critical path has the main negative impact in the speed and power consumption [13][14][15][16][17][18]. Therefore, substantial research activity has been carried out currently targeting both, application-specific integrated circuits (ASICs) [19][20][21] and FPGAs [5][6][7][8][9][10][22][23][24][25], where the minimization of the number of arithmetic operations subject to a minimum number of depth levels is the ultimate goal.…”
Section: Introductionmentioning
confidence: 99%